1991
DOI: 10.1002/ajmg.1320410317
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome of developmental retardation, facial and skeletal anomalies, and hyperphosphatasia in two sisters: Nosology and genetics of the coffin‐siris syndrome

Abstract: We report on 2 sisters, 3 and 6 years old, with a possible new syndrome consisting of developmental retardation, facial and skeletal anomalies, and hyperphosphatasia. This disorder closely resembles the Coffin-Siris syndrome (McKusick number 135900). We describe the difficulties in achieving a diagnosis. A major diagnostic clue was the radiological recognition of hypoplasia/aplasia of the terminal phalanx of the 5th finger. Minor facial anomalies and mental retardation alone had not led to the proper diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…We used the RESEARCH app of the Face2Gene suite to evaluate a classifier for the five most prevalent GPIBDs, that is PIGA (n=20), PIGN (n=11), PIGT (n=12), PIGV (n=25), and PGAP3 (n=23) at the current moment. Our original sample set thus consists of frontal facial photos of 91 individuals with a molecularly confirmed diagnosis of HPMRS or MCAHS, including cases that have been previously published [5, 9-11, 13-15, 19, 27-29, 31-33, 38, 43, 47, 49, 50, 52-56, 60, 63]. The mean accuracy that is achieved on this original sample set is 52.2 %, which is significantly better than randomly expected.…”
Section: Resultsmentioning
confidence: 99%
“…We used the RESEARCH app of the Face2Gene suite to evaluate a classifier for the five most prevalent GPIBDs, that is PIGA (n=20), PIGN (n=11), PIGT (n=12), PIGV (n=25), and PGAP3 (n=23) at the current moment. Our original sample set thus consists of frontal facial photos of 91 individuals with a molecularly confirmed diagnosis of HPMRS or MCAHS, including cases that have been previously published [5, 9-11, 13-15, 19, 27-29, 31-33, 38, 43, 47, 49, 50, 52-56, 60, 63]. The mean accuracy that is achieved on this original sample set is 52.2 %, which is significantly better than randomly expected.…”
Section: Resultsmentioning
confidence: 99%
“…Rabe et al [1991] reported two individuals who presented with delayed development, coarse facial features, a broad nose and anteverted nares, and hypoplastic fifth digits. They were both found to have elevated levels of alkaline phosphatase (>1000 U/Liter, normal < 600) unattributable to other causes.…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
“…As this syndrome's etiology remains unknown, the diagnosis is based solely on clinical findings. Both autosomal recessive and autosomal dominant inheritance have been reported [Coffin and Siris, 1970;Carey and Hall, 1978;Hersch et al, 1982;Haspeslagh et al, 1984;Franceschini et al, 1986;Richieri-Costa et al, 1986;Rabe et al, 1991;Bonioli et al, 1995].…”
Section: Introductionmentioning
confidence: 93%